2022
DOI: 10.4103/ijo.ijo_1221_22
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and treatment outcomes of an algorithmic approach to uveal effusion syndrome

Abstract: Purpose: To describe the clinical features and treatment outcomes in spontaneous uveal effusion syndrome (UES). Methods: A 10-year retrospective chart review of UES patients from a tertiary eye center was carried out. Optical coherence tomography (OCT), fundus fluorescein angiography, and ultrasound biomicroscopy (UBM) scans were performed. UES was managed based on presenting best-corrected visual acuity (BCVA), symptoms, and fundus findings. Patients with secondary cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Special anatomic features of nanophthalmos. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] zonular dialysis occurred after a cotton applicator was applied to the injection site in an effort to control the reflux of hyaluronic acid or air. The lens dislocated into the vitreous cavity in Cases 4 and 5 after the eye was reinflated with a balanced salt solution injected through a limbal incision.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Special anatomic features of nanophthalmos. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] zonular dialysis occurred after a cotton applicator was applied to the injection site in an effort to control the reflux of hyaluronic acid or air. The lens dislocated into the vitreous cavity in Cases 4 and 5 after the eye was reinflated with a balanced salt solution injected through a limbal incision.…”
Section: Resultsmentioning
confidence: 99%
“…31 Medical therapy with oral corticosteroids in uveal effusion syndrome is well established but was deemed ineffective in nanophthalmos. 10,11 Elgin et al 9 described a patient with nanophthalmos and mild exudative RD that resolved rapidly after administration of the topical corticosteroid alone. The authors suggested that the corticosteroid reduced inflammation and stabilized the blood-ocular barrier, thereby improving regression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation